Arterial Stiffness and Risk of Overall Heart Failure, Heart Failure With Preserved Ejection Fraction, and Heart Failure With Reduced Ejection Fraction: The Health ABC Study (Health, Aging, and Body Composition). Issue 2 (February 2017) - Pandey, Ambarish; Khan, Hassan; Newman, Anne B.; Lakatta, Edward G.; Forman, Daniel E.; Butler, Javed; Berry, Jarett D.
Abstract : Higher arterial stiffness is associated with increased risk of atherosclerotic events. However, its contribution toward risk of heart failure (HF) and its subtypes, HF with preserved ejection fraction (HFpEF) and HF with reduced ejection fraction (HFrEF), independent of other risk factors is not well established. In this study, we included Health ABC study (Health, Aging, and Body Composition) participants without prevalent HF who had arterial stiffness measured as carotid–femoral pulse wave velocity (cf-PWV) at baseline (n=2290). Adjusted Cox-proportional hazards models were constructed to determine the association between continuous and data-derived categorical measures (tertiles) of cf-PWV and incidence of HF and its subtypes (HFpEF [ejection fraction >45%] and HFrEF [ejection fraction ⩽45%]). We observed 390 HF events (162 HFpEF and 145 HFrEF events) over 11.4 years of follow-up. In adjusted analysis, higher cf-PWV was associated with greater risk of HF after adjustment for age, sex, ethnicity, mean arterial pressure, and heart rate (hazard ratio [95% confidence interval] for cf-PWV tertile 3 versus tertile 1 [ref] =1.35 [1.05–1.73]). However, this association was not significant after additional adjustment for other cardiovascular risk factors (hazard ratio [95% confidence interval], 1.14 [0.88–1.47]). cf-PWV velocity was also not associated with risk of HFpEF and HFrEF after adjustment for potential confounders (most adjusted hazard ratio [95% confidence interval] for cf-PWV tertile 3 versus tertile 1 [ref]: HFpEF, 1.06 [0.72–1.56]; HFrEF, 1.28 [0.83–1.97]). In conclusion, arterial stiffness, as measured by cf-PWV, is not independently associated with risk of HF or its subtypes after adjustment for traditional cardiovascular risk factors. Abstract : Supplemental Digital Content is available in the text.